2018
DOI: 10.1037/rev0000111
|View full text |Cite
|
Sign up to set email alerts
|

The dark core of personality.

Abstract: Many negatively connoted personality traits (often termed "dark traits") have been introduced to account for ethically, morally, and socially questionable behavior. Herein, we provide a unifying, comprehensive theoretical framework for understanding dark personality in terms of a general dispositional tendency of which dark traits arise as specific manifestations. That is, we theoretically specify the common core of dark traits, which we call the (). The fluid concept of D captures individual differences in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

24
370
2
16

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 358 publications
(412 citation statements)
references
References 136 publications
(225 reference statements)
24
370
2
16
Order By: Relevance
“…The link between low levels in Honesty–Humility and greedy, selfish or, more generally, antagonistic behaviour is also in line with this dimensions' negative relations with dark traits such as Machiavellianism, Narcissism and Psychopathy (Lee & Ashton, ; Muris, Merckelbach, Otgaar, & Meijer, ) and indeed the general dispositional tendency of which many different dark traits are specific manifestations, the ‘dark core of personality’ (Moshagen, Hilbig, & zettler, in press). Our findings are consistent with studies investigating the effects of dark traits in decision‐making processes.…”
Section: Discussionmentioning
confidence: 75%
“…The link between low levels in Honesty–Humility and greedy, selfish or, more generally, antagonistic behaviour is also in line with this dimensions' negative relations with dark traits such as Machiavellianism, Narcissism and Psychopathy (Lee & Ashton, ; Muris, Merckelbach, Otgaar, & Meijer, ) and indeed the general dispositional tendency of which many different dark traits are specific manifestations, the ‘dark core of personality’ (Moshagen, Hilbig, & zettler, in press). Our findings are consistent with studies investigating the effects of dark traits in decision‐making processes.…”
Section: Discussionmentioning
confidence: 75%
“…We want to make it clear that self‐compassion is just a single example of the problematic practice of proposing new constructs while simultaneously making ambiguous construct definitions and ignoring psychometric standards ranging from item development to reasonable tests of different forms of validity (cf. Moshagen, Hilbig, & Zettler, in press). With our contributions, we highlighted problematic aspects of the definition and measurement of the construct self‐compassion.…”
Section: Resultsmentioning
confidence: 99%
“…In reviewing other research that extended the DT cross-culturally, we failed to observe any disclosure of structural invariance testing (see Jonason et al, 2013Jonason et al, , 2017, or those that did reported barely "acceptable" fits (Robertson et al, 2016). They tested their conceptualization of D as a fluid construct and provided both a test and theoretical framework for understanding dark personalities (Moshagen et al, 2018). The consistency of barely acceptable model fits reported in the literature may point toward an underpinning theoretical issue with the DT framework.…”
Section: Discussionmentioning
confidence: 70%
“…We echo these calls for better measurement and more rigorous methodology. Moshagen, Hilbig, and Zettler (2018) later provided a unifying, comprehensive theoretical framework for understanding dark personality. These previous findings along with those from the present study leave us skeptical as to the reliability of extending the DT framework cross-culturally.…”
Section: Discussionmentioning
confidence: 99%